Effects of mixed organic and inorganic fertilizers application on soil properties and the growth of kenaf (Hibiscus cannabinus L.) cultivated on BRIS soils - Basri, Mohd Hadi Akbar; Abdu, Arifin; Jusop, Shamsuddin; Ahmed, Osumanu Haruna; Abdul Hamid, Hazandy; Kusno, Mohd Ashadie; Zainal, Baharom; Senin, Abdul Latib; Junejo, Nasima (Science Publications, 2013)
The demand for kenaf in the world increases rapidly by the years. Cultivation of the crop in Malaysia is a challenging task, especially when kenaf is grown on sandy soils with low fertility, such as the BRIS Soils (Beach Ridges Interspersed with Swales). A pot study was conducted in a glasshouse at Universiti Putra Malaysia to evaluate the potential of inorganic and organic fertilizers or their combination for growing kenaf on very sandy BRIS Soils, using variety V36. There were altogether sixteen treatments: (T1)-control (100% BRIS soil), (T2)-NPK (chemical fertilizer), (T3)-CM (chicken manure), (T4)-B (biochar), (T5)-Z (zeolite), (T6)-NPK+CM, (T7)-NPK+B, (T8)-NPK+Z, (T9)-CM+B, (T10)-CM+Z, (T11)-B+Z, (T12)-NPK+CM+B, (T13)-NPK+CM+Z, (T14)-CM+B+Z, (T15)-NPK+B+Z and (T16)- NPK+CM+B+Z. Results showed that application of inorganic material or organic fertilizer in combination with chemical fertilizer (T2 and T16) improved soil fertility, which are reflected by the increase inexchangeable K, Ca and Mg, CEC, total N, total C and available P. The highest kenaf growth was observed in T15 treatment.Application of biochar, zeolite or chicken manure alone on the soils did not result in better kenaf growth compared to the control. Zeolite and biochar should be applied with other fertilizers or organic substrate to obtain a positive yield of crop and increase the soil properties. In addition, more studies on the application of chicken manure at different ratios should be conducted to obtain the best yield. Combination treatment, T15 (NPK + biochar + zeolite) can be suggested to the farmers especially cultivation of kenaf on sandy BRIS soil in order to obtain the best kenaf growth performance and indirectly reduce excessive use of chemical fertilizers.